1990
DOI: 10.1037/0278-7393.16.3.374
|View full text |Cite
|
Sign up to set email alerts
|

Similarity effects in word and pseudoword repetition priming.

Abstract: Repetition priming refers to the facilitation in the visual identification of a stimulus produced by a recent encounter with that stimulus. In the paradigm used here, subjects performed a naming task in which a sequence of primes was presented; then they performed a tachistoscopic identification task in which the stimuli that were presented varied in their similarity to the primes. The results indicated that repetition priming facilitated the identification of repeated words and pronounceable nonwords that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
109
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(124 citation statements)
references
References 31 publications
11
109
4
Order By: Relevance
“…If the visual information and the conceptual information associated with a word are stored in spatially separated areas of neocortex, the representation of that word must include some links between the stores (as well as links to phonological stores). This is an idea inherent in many connectionist models of word processing (e.g., Masson, 1995;Plaut & Shallice, 1993;Rueckl, 1990;Seidenberg & McClelland, 1989;Van Orden et al, 1990). The representation of a word per se includes perceptual, conceptual, and phonological information, thus the links between the relevant subsystems are crucial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the visual information and the conceptual information associated with a word are stored in spatially separated areas of neocortex, the representation of that word must include some links between the stores (as well as links to phonological stores). This is an idea inherent in many connectionist models of word processing (e.g., Masson, 1995;Plaut & Shallice, 1993;Rueckl, 1990;Seidenberg & McClelland, 1989;Van Orden et al, 1990). The representation of a word per se includes perceptual, conceptual, and phonological information, thus the links between the relevant subsystems are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that only weak, not strong, modularity/independence is a hallmark of dissociable areas in neocortex (e.g., Farah, 1994;Van Essen & DeYoe, 1995), visual and postvisual processes may interact in important ways despite their spatial separation. For example, the visual-form representation and the conceptual representation for a word, although stored in spatially separated neocortical subsystems, may be interconnected and interactive, as in neural network models that posit separate pools of units for representing visual and postvisual information for words yet also posit a high degree of interactivity between pools when processing words (e.g., see Masson, 1995;Plaut & Shallice, 1993;Rueckl, 1990;Seidenberg & McClelland, 1989;cf. Van Orden, Pennington, & Stone, 1990).…”
Section: Interactive Visual-postvisual Processesmentioning
confidence: 99%
“…As semantic priming produces a performance advantage for related trials (Neely, 1991), and repetition priming produces a performance advantage for repeated items (Durgunoglu, 1988;Forster & Davis, 1984;Rueckl, 1990), it would be expected that repeated word presentation should result in larger semantic priming effects. However, studies have demonstrated that the repeated presentation of primes actually eliminates semantic priming effects in lexical decision tasks (Neely et al, 1998;Pitzer & Dagenbach, 2001).…”
mentioning
confidence: 99%
“…This word repetition effect has been demonstrated using a number of procedures including, for example, lexical decision (Forbach, Stanners, & Hochhaus, 1974), word naming (Scarborough, Cortese, & Scarborough, 1977), perceptual identification (Jacoby & Dallas, 1981), recognition tasks (Ratcliff, Hockley, & McKoon, 1985) and can be observed when repetition is made seconds, minutes, hours, or days apart (Feustel, Shiffrin, & Salasoo, 1983;Salasoo, Shiffrin, & Feustel, 1985;Scarborough, et ul., 1977), or even when subjects are not aware of the first presentation of the stimulus (Forster, Booker, Schacter, & Davis, 1990). Two broad theoretical accounts are given to explain such repetition priming phenomena: we will refer to them as lexical or semantic account and the episodic memory interpretation (see, for example, Forster, et al, 1990;Masson & Freedman, 1990;Rueckl, 1990;Woltz, 1990).…”
mentioning
confidence: 99%
“…This word repetition effect has been demonstrated using a number of procedures including, for example, lexical decision (Forbach, Stanners, & Hochhaus, 1974) McKoon, 1985) and can be observed when repetition is made seconds, minutes, hours, or days apart (Feustel, Shiffrin, & Salasoo, 1983;Salasoo, Shiffrin, & Feustel, 1985; Scarborough, et ul., 1977), or even when subjects are not aware of the first presentation of the stimulus (Forster, Booker, Schacter, & Davis, 1990). Two broad theoretical accounts are given to explain such repetition priming phenomena: we will refer to them as lexical or semantic account and the episodic memory interpretation (see, for example, Forster, et al, 1990; Masson & Freedman, 1990;Rueckl, 1990;Woltz, 1990).The former theoretical account of the word repetition effect is based on the assumption that presentation of a word is capable of inducing the activation of its lexical representation. In word detector models (see, for example, Morton, 1979) faster performance on repeated trials is attributed to residual activation or lower thresholds of existing lexical or semantic memory codes for stimulus words.…”
mentioning
confidence: 99%